Algorithm Domination As A New Surveillance System - Ahmet Ayhan Koyuncu; Muhittin Evren (Yeni Medya)
This study emphasizes that surveillance differs in digital process. The study draws attention to how surveillance systems work in the new process. With the development of digital technologies, surveillance and control, which spread over a wide area, greatly affect people's lives. People's information is recorded, analyzed, and used to direct people. The study draws attention to the fact that this structure works through algorithms. Algorithms form a surveillance and control mechanism with their processing way. Algorithms constitute a domination form because they threaten people's freedoms and security. Algorithm domination is seen as a form of control and discipline in today's world. The study analyzes the domination forms created by algorithms that influence and are debated in today's world. It profiles people thanks to the information obtained with big data. In this way, people can be easily manipulated and directed by algorithms. The study aims to reveal how algorithm domination occurs and how it works from a theoretical perspective.